2013
DOI: 10.1002/jssc.201300085
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dispersive liquid-liquid microextraction with central composite design for preconcentration of chlordiazepoxide drug and its determination by HPLC-UV

Abstract: A simple, rapid, and sensitive method based on dispersive liquid-liquid microextraction combined with HPLC-UV detection applied for the quantification of chlordiazepoxide in some real samples. The effect of different extraction conditions on the extraction efficiency of the chlordiazepoxide drug was investigated and optimized using central composite design as a conventional efficient tool. Optimum extraction condition values of variables were set as 210 μL chloroform, 1.8 mL methanol, 1.0 min extraction time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…To study the effect of the extracting solvent volume, different volumes of carbon tetrachloride (15,20,25, and 30 L) were used using the same extraction procedure. The results obtained showed that by increasing the volume of carbon tetrachloride from 15 to 30 L, the analytical signals decreased rapidly.…”
Section: Volume Of Extracting Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the effect of the extracting solvent volume, different volumes of carbon tetrachloride (15,20,25, and 30 L) were used using the same extraction procedure. The results obtained showed that by increasing the volume of carbon tetrachloride from 15 to 30 L, the analytical signals decreased rapidly.…”
Section: Volume Of Extracting Solventmentioning
confidence: 99%
“…In 2006, a rapid, simple, and low‐cost LPME method with a high enrichment factor, namely, dispersive LLME, was proposed . It immediately gained considerable attention from researchers . However, it is based upon a ternary component solvent system, in which utilization of the cosolvents (disperser solvents) leads to some disadvantages such as decrease in the partition coefficients for extraction of the analytes into the extracting solvent and increase in the cost and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The N-oxide type molecules can be found in several active pharmaceutical ingredients (such as: Chlordiazepoxide as sedative, [2] Tirapazamine as anticancer, [3] Phenazopyridine, [4] Flupirtine, [5] Propirame [6] as analgestic, Phenyramidol muscle relaxant [7]) (Figure 1), in addition N-oxides are typical metabolic intermediates in the human organism, so the synthetic preparation of those N-oxides from tertiary amines has a high importance in drug development [8].…”
Section: N-oxide Derivativesmentioning
confidence: 99%
“…Although these miniaturize sample pretreatment techniques are rapid, easy, and minimize the use of organic solvents, but suffer from some problems such as sample carryover, fiber fragility, high operational time, and relatively low precisions . To overcome these limitations, dispersive liquid–liquid microextraction (DLLME) was introduced with some advantages including rapidity, low cost, simple operation, and high preconcentration factor . Despite the many benefits of DLLME, the choice of the extraction solvent is still a drawback.…”
Section: Introductionmentioning
confidence: 99%